Low Mass Stars or Intermediate Mass Stars? The Stellar Origin of Presolar Oxide Grains Revealed by Their Isotopic Composition - Palmerini, S.; Cristallo, S.; Busso, M.; La Cognata, M.; Sergi, M. L.; Vescovi, D. (Frontiers in Astronomy and Space Sciences, 2021)
Among presolar grains oxide ones are made of oxygen, aluminum and a small fraction of Magnesium, produced by the 26Al decay. The largest part of presolar oxides belong to the so called group 1 and 2, which have been suggested to form in RGB and AGB stars, respectively. However, standard stellar nucleosynthesis models cannot account for the 17O/16O, the 18O/16O and the 26Al/27Al values recorded in those grains. Hence, for more than twenty years the occurrence of mixing phenomena coupled with stellar nucleosynthesis have been suggested to account for this peculiar isotopic mix. Nowadays, models of massive AGB stars experiencing Hot Bottom Burning or low mass AGB stars where Cool Bottom Process, or other kind of extra-mixing, is at play, nicely fit the oxygen isotopic mix of group 2 oxide grains. The largest values of the 26Al/27Al ratio seem somewhat more difficult to be accounted for.